The Effects of Enhancement Strategies of Beef Flanks on Composition and Consumer Palatability Characteristics - Andrea J. Garmyn; J. Chance Brooks; Markus F. Miller; Nicholas C. Hardcastle; Sean J. Morrow (Meat and Muscle Biology, 2019)
Beef rectus abdominis muscles (n = 100; 20/treatment) were assigned randomly to 1 of 5 treatments: untreated control (Control, No Treatment; CNT), vacuum tumbled control without marinade (Tumbled Control, No Treatment; TCNT), vacuum tumbled with marinade (TUMB), injected with marinade (INJ), and injected with marinade plus vacuum tumbled (IPT) to determine how enhancement techniques influence consumer palatability. After processing, flank samples were cooked (72°C), cut into 1.3-cm strips, and served as fajita strips for consumer evaluation (n = 200). Treatment influenced (P < 0.01) the rating and acceptability of all palatability traits, overall liking, and willingness to pay (WTP). Consumers scored IPT and INJ more tender compared to all other treatments (P < 0.05). Samples processed using IPT and INJ were juicier (P < 0.05) than all other treatments, except INJ and TUMB were similar (P > 0.05). Samples processed using TUMB and INJ were similar (P > 0.05) for flavor and WTP, and INJ, IPT, and TUMB samples were similar (P > 0.05) for overall liking. Thus, consumers were willing to pay more for IPT than TUMB (P < 0.05). Consumers scored CNT and TCNT lower for all palatability traits which resulted in lower WTP (P < 0.05). Inclusion of a marinade improved the eating quality of samples compared to CNT and TCNT. The delivery method of the brine solution was less important to palatability as the presence of a marinade, as IPT, INJ, and TUMB were all similar (P > 0.05) for overall liking. Injection plus tumbling improved tenderness, juiciness, and flavor liking scores over tumbling alone, but not over injection alone. Injection influenced consumer tenderness more than tumbling, but tumbling had greater effects on cooked moisture than injection. While IPT did not surpass either TUMB or INJ in all sensory categories, IPT does excel when considering moisture retention along with palatability.